The Impact of Fossil Fuel Energy, Technological Innovation and Globalization on Tourism Inflows of Top Ten Most Visited Countries - Jabeen, Samrena; Nasim, Ismat; Bashir, Furrukh; Chaloupský, David; Akbar, Ahsan (International Journal of Energy Economics and Policy, 2024)
Increased uses of fossil fuel consumption, globalization, and tourism activities have significant adverse effects on the sustainability of our ecosystem. The present study takes into account the top 10 most visited nations by tourists to examine the impact of fossil fuel energy consumption, technological innovation, foreign direct investment (FDI), economic growth, and globalization on tourism inflows from 2008 to 2022.. Choice of appropriate technique for empirical testing is based on the PP-Fisher, ADF Fisher, IPS, and LLC unit root tests. Due to mixed order of integration of variables, the Panel ARDL is more reliable for econometric investigation. The findings of Panel ARDL reveal that the most significant contributing factors towards growth in tourism are technological innovation, the globalization index, growth in gross domestic product, and use of fossil fuels as an energy source. These results imply that advancements in technology, increased globalization trends, and economic growth are facilitating the growth in tourism activities. Likewise, non-renewable energy consumption is significantly linked to tourism growth in these countries which exhibits that these governments are relying upon fossil fuel consumption to meet the energy demand for tourism activities and to fuel economic growth. Though, FDI is having a detrimental effect on tourism inflows in the top 10 most frequently visited nations. This outcome entails that expanded industrialization and economic footprint negatively influence the ecological environment which adversely affects tourism inflows. The policy implications of this research assert that the development of clean and renewable energy technologies is essential for the promotion of sustainable economic growth, promote eco-tourism in these countries. Similarly, smart manufacturing and environment friendly production can alleviate the negative effects of ecological footprint on tourism inflows.